2020
DOI: 10.18410/jebmh/2020/36
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphological Spectrum of Ovarian Tumours, 4 Years Experience in a Regional Institute

Abstract: BACKGROUND Worldwide, ovarian cancer is the sixth most common cancer in women and seventh most common cause of cancer death. For most western countries, ovarian cancer is the fifth most common cancer and ranks fourth in cancer mortality. For the western hemisphere it accounts for 4% of cancer in women and is the most frequent cause of death due to gynaecological cancer; whereas, in some European countries, and in parts of Eastern India, ovarian cancer is reported as the most frequent cause of death in women fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
0
0
Order By: Relevance
“…Among 62 cases of ovarian tumours, most cases belonged to the 31-40 years age group. This is consistent with studies done by Patel et al, Devi et al, Garg et al, and Pilli et al 12,[14][15][16] We found abdominal pain in 70.9% of cases as the most common presenting complaint followed by menorrhagia in 9.8% and abdominal distension in 4.1%. Gonsai et al found these findings in 52%, 16% and 18% of cases respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Among 62 cases of ovarian tumours, most cases belonged to the 31-40 years age group. This is consistent with studies done by Patel et al, Devi et al, Garg et al, and Pilli et al 12,[14][15][16] We found abdominal pain in 70.9% of cases as the most common presenting complaint followed by menorrhagia in 9.8% and abdominal distension in 4.1%. Gonsai et al found these findings in 52%, 16% and 18% of cases respectively.…”
Section: Discussionsupporting
confidence: 93%
“…2 In Eastern India, including Manipur, cervix uteri (9.5%) and ovarian cancer are among the most prevalent causes of death in women from gynaecological cancer. 3 Gynaecological cancer poses significant challenges, deeply affecting a woman's life and her family dynamics. It impacts femininity, fertility, sexuality, physical and mental health, social relationships, and work-life balance, ultimately diminishing the overall quality of life.…”
Section: Introductionmentioning
confidence: 99%